PERAN GURU BK DALAM MENCEGAH PERILAKU SELF-HARM PADA REMAJA SEKOLAH MENENGAH - Keysah Ramadian; Yolanda Ayu Kirana; Gusman Lesmana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Self-harming behavior among adolescents is an increasingly alarming mental health issue in secondary schools, both in Indonesia and globally. This article aims to comprehensively examine the role of Guidance and Counseling (BK) teachers in the prevention and management of selfharming behavior in secondary school settings. Using a systematic literature review approach, this study analyzes various relevant scientific sources, including qualitative and quantitative studies, systematic reviews, and meta-analyses published between 2019 and 2024. The results indicate that guidance and counseling teachers occupy a strategic position as the first line of defense in detecting, supporting, and referring students exhibiting self-harming behaviors. Several counseling approaches have proven effective, including behavioral, psychoanalytic, and cognitive-behavioral approaches. However, the effectiveness of school counselors’ role also depends on several supporting factors, such as training, emotional competence, and skills in managing compassion fatigue. Furthermore, collaboration among school counselors, parents, mental health professionals, and the entire school community is a critical prerequisite for creating a comprehensive prevention system. This article offers practical implications